A comparative human rights analysis of laws and policies for adolescent contraception in Uganda and Kenya - Katrina Perehudoff; Denis Kibira; Elke Wuyts; Carles Pericas; Joyce Omwoha; Hendrika A. van den Ham; Aukje K. Mantel-Teeuwisse; Kristien Michielsen (BMC, 2022)
Plain language summary The unmet need for contraception among adolescents is high in Uganda and Kenya, and has many negative consequences, including unwanted pregnancy, exposure to unsafe abortion, and maternal morbidity and mortality. National laws and policies play an important role in determining adolescents' access to contraception. For example, national laws and policies can shape the government programs that provide (or withhold) contraception, and the social norms influencing adolescents' access to contraception. Therefore, this research compares national laws and policies that determine access to contraception services and information for adolescents in Uganda and Kenya with WHO's recommendations for access to contraception. This is an analysis of the content of Ugandan and Kenyan laws and policies in force between 2010 and 2018. The content of these documents was analyzed using WHO's nine recommendations for how contraception information and services should be provided: non-discrimination, availability, accessibility, acceptability, quality, informed decision-making, confidentiality, participation, accountability. Ninety-three documents were screened and 26 documents were included in the analysis: 13 policies from Uganda and 13 policies from Kenya. On average, Ugandan policies include one WHO recommendation for adolescent contraception per policy and Kenyan policies include two WHO recommendations. This recommendation most frequently mentioned in all policies is the accessibility of contraception (for example, for adolescents living remotely, integrated in adolescent HIV or pre-/post-natal care, etc.). Together, all Ugandan policies mentioned 6/9 WHO recommendations whereas all Kenyan policies cover 8/9 WHO recommendations. In conclusion, Ugandan and Kenyan policies are consistent with many of WHO's recommendations for access to contraception, however, there is still room for improvement.